2018
DOI: 10.3390/rel9030072
|View full text |Cite
|
Sign up to set email alerts
|

Religious Beliefs and Environmental Behaviors in China

Abstract: The role of religion in the environment has yet to be empirically investigated in the country with the largest atheist population across the globe. Using data from the Chinese General Social Survey 2013, we examined the effects of religious beliefs on environmental behaviors in China. Dependent variables of private and public environmental behaviors were identified by factor analysis. The estimation revealed a contradictory result that most religious beliefs had negative effects on private environmental behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…This ranking is supported by Gutsche [60], since this paper finds a significant impact of Christianity (i.e., Catholics and Protestants) only for minor pro-environmental behaviors, such as purchases of food and clothes; but it is in contrast with Hwang [61], where CHR > BUD, although this paper refers to pro-environmental intentions rather than observed behaviors. This ranking is partially supported by Arli and Tjiptono [62] (i.e., ISL > CHR) for impacts of intrinsic religiousness on attitudes towards environmental issues; and it is partially confirmed by Yang and Huang [63] (i.e., BUD > CHR) for public pro-environmental behaviors, such as donating to environmental protection, and participating in environmental activities organized by governmental and non-governmental organizations. Finally, the statistical results confirm the theoretical insights on Judaism (i.e., a less negative impact on sustainability) and on Christianity (i.e., a non-significant impact on sustainability).…”
Section: Appendix D Statistical Resultsmentioning
confidence: 84%
“…This ranking is supported by Gutsche [60], since this paper finds a significant impact of Christianity (i.e., Catholics and Protestants) only for minor pro-environmental behaviors, such as purchases of food and clothes; but it is in contrast with Hwang [61], where CHR > BUD, although this paper refers to pro-environmental intentions rather than observed behaviors. This ranking is partially supported by Arli and Tjiptono [62] (i.e., ISL > CHR) for impacts of intrinsic religiousness on attitudes towards environmental issues; and it is partially confirmed by Yang and Huang [63] (i.e., BUD > CHR) for public pro-environmental behaviors, such as donating to environmental protection, and participating in environmental activities organized by governmental and non-governmental organizations. Finally, the statistical results confirm the theoretical insights on Judaism (i.e., a less negative impact on sustainability) and on Christianity (i.e., a non-significant impact on sustainability).…”
Section: Appendix D Statistical Resultsmentioning
confidence: 84%
“…In this article, we mainly use religious identity as a predictor of religion. After carefully reviewing the current studies on religion and environmental behavior in China and the West, we found that some scholars have focused on the natural relationship between religion and environmental behavior (Woodhouse et al 2015;Du et al 2014;Yang and Huang 2018). However, whether there are group differences in the influence of religion on environmental behavior remains to be further discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, we found that political participants with a religious identity are more willing to participate in public pro-environmental behavior than those without a religious identity and religious people who exhibit political participation are more willing to engage in public pro-environmental behavior. Some scholars have confirmed that there is a connection between religion and politics (Yang and Huang 2018). It is not too difficult to find that political participants will pay attention to various public issues, including environmental protection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations